2021
DOI: 10.48550/arxiv.2105.08727
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Radio galaxies in galaxy groups: kinematics, scaling relations and AGN feedback

T. Pasini,
A. Finoguenov,
M. Brüggen
et al.

Abstract: We investigate the kinematic properties of a large (N=998) sample of COSMOS spectroscopic galaxy members distributed among 79 groups. We identify the Brightest Group Galaxies (BGGs) and cross-match our data with the VLA-COSMOS Deep survey at 1.4 GHz, classifying our parent sample into radio/non-radio BGGs and radio/nonradio satellites. The radio luminosity distribution spans from L R ∼ 2 × 10 21 W Hz −1 to L R ∼ 3×10 25 W Hz −1 . A phase-space analysis, performed by comparing the velocity ratio (line-of-sight … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Large offsets (100-1000 kpc) are often an indication of a strongly disturbed cluster environment (Rossetti et al 2016;De Propris et al 2021, and references therein). The relation between BCGs, the triggering of the AGN and the offset from the cluster centre has been widely discussed and was recently studied in Pasini et al (2021a). In that paper, the authors found that it is more common for more central BCGs to show radio-loud AGN since in these galaxies the accretion onto the central BH is boosted by the strong cooling in the cluster core.…”
Section: Bcg Offsetsmentioning
confidence: 99%
See 1 more Smart Citation
“…Large offsets (100-1000 kpc) are often an indication of a strongly disturbed cluster environment (Rossetti et al 2016;De Propris et al 2021, and references therein). The relation between BCGs, the triggering of the AGN and the offset from the cluster centre has been widely discussed and was recently studied in Pasini et al (2021a). In that paper, the authors found that it is more common for more central BCGs to show radio-loud AGN since in these galaxies the accretion onto the central BH is boosted by the strong cooling in the cluster core.…”
Section: Bcg Offsetsmentioning
confidence: 99%
“…They also discuss a correlation between the X-ray luminosity of groups and the radio power from the central radio galaxy since more massive groups seem to host more powerful sources. Indeed, Pasini et al (2021a) recently showed that, in their sample of groups, BGGs showing powerful radio emission are always found within 0.2 R vir ∼ 0.3R 200 from the centre.…”
Section: Introductionmentioning
confidence: 99%
“…Using x-ray observations with the Chandra and XMM-Newton, Ineson et al (2015) shows that there are strong correlations between the radio luminosity and cluster luminosity for LERGs, though not for HERGs; however, these results are restricted to the most luminous clusters. It is expected that the luminosity of the central radio galaxy scales with the X-ray luminosity of the cluster (Pasini et al 2020(Pasini et al , 2021, implying that brighter radio galaxies populate richer environments (Best 2004;Ching et al 2017;Croston et al 2018).…”
Section: Introductionmentioning
confidence: 99%